Making an Expert System in Diagnosing Eye Disease Using the Forward Chaining Method [Pembuatan Sistem Pakar Dalam Mendiagnosis Penyakit Mata Dengan Menggunakan Metode Forward Chaining] - Hermawan, Tunggal; Eviyanti, Ade (Indonesian Journal of Applied Technology, 2024)
In the wider community not all know about eye disease. Due to limitations in medical knowledge and difficulties in transportation and the distance to go to an ophthalmologist, many people with eye diseases do not get proper and fast treatment. That's why we need an application that can make a diagnosis like an ophthalmologist. Therefore, an expert system application for diagnosing eye diseases using the forward chaining method was made. Forwaid Chaining is used because it can diagnose eye diseases from various existing symptoms. The results of the diagnosis with the forward chaining method can provide results in the form of conclusions based on symptoms of the type of disease. Diagnosis eye diseases using the forward chaining method also provides solutions for eye diseases and solutions for treating eye diseases with a diagnosis of 70%.